An Analysis of Selected Economic, Social, and Fiscal Indicators for Nonmetropolitan School Classification Schemes - Richard J. Reeder (Journal of Research in Rural Education, 1992)
Any classification system ofrural school districts should take into account the socioeconomic environment in which school districts must operate. Here, I examine some of the most common economic, social, and fiscal indicators available from federal data sources. My focus is on potential problems that might occur because of data limitations, such as unintentional biases favoring certain types of places and the lack of timely data. I conclude that such problems neednot rule out the use of these indicators in a classification scheme, since many ofthese indicators have strengths that outweigh their weaknesses. Nevertheless, researchers shouldbe aware ofthe problems ofparticular indicators, and, where possible, use multiple indicators or alternative data sources to mitigate these problems.